Effect Of Online Shopping On Consumtive Behavior In Pandemic Time Covid-19 - et. al., Rini Handayani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Covid-19 pandemic has changed the shopping behavior of Indonesians, who previously shopped offline at physical outlets, are now starting to switch to shopping online. However, shopping online with the convenience offered and at various prices can shape consumptive behavior.The purpose of this study was to determine the perception of online shopping, the consumptive behavior of the millennial generation during the Covid-19 pandemic, and its effectsThe research method used is descriptive and verification. Data collection techniques through questionnaires, interviews and observations. The sample in this study is millennial generation consumers who have shopped at Shopee's online shop, with a minimum sample of 100 respondents.The analysis tool uses simple regression. The results of statistical tests state that there is an effect of millennial generation online shopping on consumptive behavior during the Covid-19 pandemic.